372 Pediatric Abusive Head Trauma During the First Year of Covid-19. (1st April 2022) - Singer, Timothy; Mehl, Steven; Kralik, Stephen; Desai, Nilesh; Orman, Gunes; Sarpong, Kwabena; Donaruma, Marcella; Cain, Cary; Warner, Claire; Huisman, Thierry; Naik-Mathuria, Bindi; Weiner, Howard L.; et al.
Abstract : INTRODUCTION: During the Covid-19 pandemic parental burnout was associated with increases in child abuse. However, the effects of the pandemic on Abusive Head Trauma (AHT) have not yet been described. METHODS: We included all patients <5 years old with expert-confirmed AHT at our freestanding children's hospital from 3/2018-2/2021. Demographic and clinical data were excerpted, and pediatric neuroradiologists reviewed neuroimaging. Descriptive and inferential analyses were conducted with RStudio. Early morbidity was assessed using gross-motor milestones and developmental quotients with the Capute Scales (CAT/CLAMS). RESULTS: 103 patients suffered AHT (64 pre-Covid-19, 39 Covid-19). The Covid-19 cohort was younger (median age 115 v. 152 days, p=0.027) and lived in homes with higher maternal unemployment (51% v. 22%, p=0.003), smaller spaces (apartments 56% v. 31%, p=0.043) and more people (median 5 v. 4, p=0.047). Clinical findings including Glasgow Coma Scale, Injury Severity Score, and multi-organ injury were similar. Neurosurgical intervention was similar (31% v. 20%, p=0.23). Neuroimaging found that during Covid-19 children suffered more extensive sub-arachnoid hemorrhage (32% v 14%, p=0.040) and spinal hemorrhage (6/39 v. 3/64 cases, p=0.046). Notably, mortality was 19% in both groups (p=0.92). During Covid-19 children removed from parental care were more likely to be placed with relatives (61% v. 36%, p=0.039) versus foster care (8.3% v. 30%, p=0.039). At 2-month follow-up, no differences were observed in new motor (43% v. 54%, p=0.45), language (33% v. 18%, p=0.59), or cognitive (36% v. 48%, p=0.36) developmental delays nor in severity of new deficits. CONCLUSION: Pediatric AHT is a serious public health problem and occurs especially at times of high family stress.(3) During Covid-19 children suffering AHT were younger and more likely to live in homes experiencing greater socioeconomic stressors compared with pre-pandemic levels.